PANDANGAN SOSIAL EKONOMI DAN KEAGAMAAN MASYARAKAT PETANI DI JAWA - Nur Khoiriyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
The life of the farming community is still very far from prosperous. This is evident from the data presented statistically relevant data on poverty and education levels. With such reality is, there should be a variety of efforts to resolve this problem. The resolution attempts to start the real state of the farming communities, for that, this article will provide an overview of the socio-economic and religious views of the farming community in the literature. Based on this basis, the author tries to give a deeper formulation related to the farming community problem solving.